PERILAKU MASYARAKAT DALAM MEMBUANG SAMPAH DI BANTARAN SUNGAI MANTUNG KECAMATAN BEO KABUPATEN KEPULAUAN TALAUD - MAHDA, REYNHARD; POSUMAH, JOHNNY HANNY; LALOMA, ALDEN (Sam Ratulangi University, 2019)
The behavior of the people in the environment and preserving the environment is very minimal.The lack of sensitivity and awareness of the community towards the environment gave birth toenvironmental conditions that had a negative impact on humans themselves. The purpose of this studywas to determine the causes of people's behavior in disposing of garbage on the banks of the MantungRiver, Beo District. This study uses descriptive qualitative research methods. The technique of collectingdata used is observation, interviews and data collection with documents. To see how people behave indisposing of garbage on the banks of the Mantung River, Beo District. The researcher used threeindicators, namely: knowledge, attitudes and actions. Based on the results of this study, it was stated thatthe behavior of people in disposing of garbage on the banks of the Mantung River in Beo Subdistrict interms of knowledge, attitudes and actions was still not good because the community did not know andunderstood well the importance of maintaining riverbanks. The community is also indifferent and does notcare about the cleanliness of the Mantung River. It can be concluded that the behavior of the communityin disposing of garbage on the banks of the Mantung River in Beo District is still not good.Keywords: Community Behavior, Cleanliness and River Banks.